2020
DOI: 10.1088/1361-6528/aba13e
|View full text |Cite
|
Sign up to set email alerts
|

Strain-induced vibrational properties of few layer black phosphorus and MoTe2 via Raman spectroscopy

Abstract: We studied and compared the effect of tensile strain on the Raman spectra of black phosphorus (BP) and molybdenum ditelluride (MoTe2) crystals by using a simple custom strain device. In-situ Raman spectroscopy on BP revealed clear red shifting of all three phonon modes, A1 g, B2g and A2 g, under tensile stress. From our theoretical analyses, we found that such red shifting strongly depends on the direction of the strain exerted on the system even within the elastic deformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 41 publications
8
19
0
Order By: Relevance
“…Feshin et al reported that the coordination of N(CH 3 ) 3 to GeCl 4 causes the electron density redistribution to elongate the Ge-Cl bond length and increase the polarity of the Ge-Cl bond [ 41 ]. It is generally accepted that the red-shifts of Raman peaks can be interpreted as a decrease in the force constant of chemical bonds, since the frequency is proportional to the square root of the force constant [ 42 ]. Therefore, it could be analogically assumed that the N:→Ni dative bond formation makes the Ni-Cl bond of NiCl 2 weaker and more polar and, hence, more reactive.…”
Section: Resultsmentioning
confidence: 99%
“…Feshin et al reported that the coordination of N(CH 3 ) 3 to GeCl 4 causes the electron density redistribution to elongate the Ge-Cl bond length and increase the polarity of the Ge-Cl bond [ 41 ]. It is generally accepted that the red-shifts of Raman peaks can be interpreted as a decrease in the force constant of chemical bonds, since the frequency is proportional to the square root of the force constant [ 42 ]. Therefore, it could be analogically assumed that the N:→Ni dative bond formation makes the Ni-Cl bond of NiCl 2 weaker and more polar and, hence, more reactive.…”
Section: Resultsmentioning
confidence: 99%
“…[ 191 ] The strain‐induced Raman shift is less in 1T‐MoTe 2 and 2H‐MoTe 2 than BP, possibly due to the relatively smaller Young's modulus. [ 192 ] An experimental study by our group has shown that under an off‐axis tensile strain, the Raman intensity of GaSe flake is suppressed in the strain direction. [ 193 ] The intrinsic fourfold‐symmetry of the E 2g 1 mode in angle‐dependent Raman spectra is tuned to a twofold‐symmetry (Figure 8e).…”
Section: Modulation Of Optical Anisotropymentioning
confidence: 99%
“…[191] The strain-induced Raman shift is less in 1T-MoTe 2 and 2H-MoTe 2 than BP, possibly due to the relatively smaller Young's modulus. [192] An experimental study by our group has shown that under an off-axis [199] Copyright 2018, American Physical Society. b) Schematic of the patterned BP nanoribbon and c) its optical absorption spectrum for x-and y-polarized light.…”
Section: Strainmentioning
confidence: 99%
“…As Raman spectroscopy does not require any sample preparation, it has been extensively used as a non-invasive, contact-less, fast and accurate tool to determine strain [43], doping effects [13], layer number [17,44], crystal orientation [45], structural transitions between different polytypes [9,[11][12][13][14][46][47][48] in fewlayer MoTe 2 devices in ambient as well as different sample environments. Furthermore, Raman scattering has been employed in various 2D materials to measure electron-phonon coupling (EPC) that governs electronic transport properties [31,32].…”
Section: Introductionmentioning
confidence: 99%